The Effect of Six-weeks Home-based Toe-in Walking Exercise on Single Leg Hope Test and Figure of Eight Test Records in Subjects with Anterior Cruciate Ligament Injury: Pilot Study - Mahshid Khaleghi-Panah; Javad Sarafzadeh; Zahra Sadat Rezaeian (Vesnu Publications, 2015)
Introduction: Anterior cruciate ligament injury is more common than injury to other knee ligaments. The primary goal of the rehabilitation for anterior cruciate ligament injury is to restore subject' function. In spite of the variety of researches concerning changes in the gait following toe-in walking exercise, no study to date has investigated its clinical effect in subjects with anterior cruciate ligament injury. Present study was aimed to determine the effect of six-week home based supervised toe-in walking exercise on function of non-coper anterior cruciate ligament deficient subjects in single hope test and figure of 8 test. Materials and Methods: Seven young non-coper men suffering from anterior cruciate ligament injury were selected according to the criteria introduced by Fitzgerald. The participants get training for to-in walking. They were instructed to walk at home with shoes for 30 minutes every day, 7 days a week for 6 weeks. Subjects' function in single hope test and figure of eight test was recorded. In addition, all the participants were requested to fill the International Knee Documentation Committee (IKDC) before and after training program. Results: Quadriceps strength (P = 0.05), single hope test score (P = 0.04) and figure of 8 test score (P = 0.001) improved significantly following six weeks of to-in walking program at home. The improvement in limb symmetry index and IKDC score were not statistically significant. Conclusion: It seems that the suggested training program may improve function of subjects suffering from anterior cruciate ligament injury.